Analisis Dampak Sosial dari Implementasi Program Pengabdian Berbasis Teknologi di Pedesaan - Guntur Suryo Putro; Arfiany Arfiany; Yasni Yasni (ABDI DAYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
This study analyzes the social impact of technology-based community service programs in rural areas. It examines how these programs improve access to education, healthcare, and economic opportunities while fostering social cohesion. The implementation of digital platforms in education has enhanced academic performance by providing high-quality resources and remote learning tools. In healthcare, telemedicine and mobile health applications have significantly increased access to medical services and improved health outcomes. Economic development has been stimulated through e-commerce platforms and digital financial services, boosting local businesses and financial inclusion. Additionally, these programs have strengthened community bonds and improved local governance through better connectivity. However, challenges such as inadequate infrastructure and low digital literacy remain, which need to be addressed for sustainable impact. The findings suggest that overcoming these barriers and engaging local stakeholders are crucial for maximizing the benefits of technology-based community service programs in rural settings.